Factors Determining the Autonomy of the Medical Resident in the Hierarchical Structure of Lithuanian Doctors - Vaitkienė, Agota (Socialinė teorija, empirija, politika ir praktika, 2023)
The purpose of this paper is to analyze the factors determining the autonomy of the medical resident in the hierarchical structure of Lithuanian doctors.Due to the different legal practices that have a direct impact on the autonomy of the medical resident, a three-level model is constructed: macro, meso, micro, according to which the impact of the system on the autonomy of the medical resident is analyzed. At the meso level, the requirements and regulations of the macro level affect the individual on micro level by creating an environment for acceptable relationships and actions.At the macro level, health care system organizations recognize the medical resident as a specialist and coordinate residency by implementing laws. According to the Medical Practice Act, which defines a medical resident, medical residents must follow the instructions of a residency supervisor or other professional until they complete their training. The autonomy of the medical resident is influenced both by the medical community due to its low hierarchical position and by health care system organizations that control the regulation of medical residency itself.The position of a student directs the medical resident to practical learning, when only acquired additional qualifications grant the license of a medical specialist, and the status of an employee in the residency bases enables direct participation in the Lithuanian medical community through working relationships. Participating in direct relationships with doctors is part of the professionalization process, when the social norms of doctors are adopted and competences are acquired. Due to the hierarchical structure of the medical community, medical residents, as holders of only the first license, are at the bottom of the hierarchy and do not have extensive autonomy to make their own decisions.
Keywords: Autonomy; medical residency; systemic model; Lithuanian medical community